2020
DOI: 10.1161/circheartfailure.119.006798
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Cardiac Rehabilitation and Long-Term Prognosis in Patients With Heart Failure

Abstract: Background: Exercise-based cardiac rehabilitation (CR) improves health-related quality of life and exercise capacity in patients with heart failure (HF). However, CR efficacy in patients with HF who are elderly, frail, or have HF with preserved ejection fraction remains unclear. We examined whether participation in multidisciplinary outpatient CR is associated with long-term survival and rehospitalization in patients with HF, with subgroup analysis by age, sex, comorbidities, frailty, and HF with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
124
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 48 publications
2
124
1
Order By: Relevance
“…Kamiya et al reported that the multidisciplinary team approach, including exercise and patient education, is effective in patients with heart failure. 23 The combination of interventions must have resulted in higher motivation and better self-management skills, and consequently a reduction in the risk of all-cause mortality and acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Kamiya et al reported that the multidisciplinary team approach, including exercise and patient education, is effective in patients with heart failure. 23 The combination of interventions must have resulted in higher motivation and better self-management skills, and consequently a reduction in the risk of all-cause mortality and acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…35 On the other hand, outpatient cardiac rehabilitation participation was associated with reduced risks of all-cause death and HF rehospitalization in frail patients with HF. 36 A new trial, the REHAB-HF study, is currently underway, and this pilot study has shown that rehabilitation therapy beginning in the hospital improved 6MWD and SPPB score, with the strongest trend seen with chair stands, in hospitalized older patients with HF, and the change in SPPB score was strongly related to all-cause rehospitalization. 37 Tissue oxygenation is decreased by anaemia and hypoxia, which may lead to functional impairment of muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of intravenous iron therapy in acute HF is not yet clear, a new trial, AFFIRM‐AHF, is currently underway with the composite of recurrent HF hospitalizations and cardiovascular mortality as the primary outcome 35 . On the other hand, outpatient cardiac rehabilitation participation was associated with reduced risks of all‐cause death and HF rehospitalization in frail patients with HF 36 . A new trial, the REHAB‐HF study, is currently underway, and this pilot study has shown that rehabilitation therapy beginning in the hospital improved 6MWD and SPPB score, with the strongest trend seen with chair stands, in hospitalized older patients with HF, and the change in SPPB score was strongly related to all‐cause rehospitalization 37 …”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive cardiac rehabilitation programs have been shown to improve the prognosis of patients with HF [6][7][8], although their efficacy for "very elderly" individuals and their impact on improving ADL are unknown. Thus, we conducted a registry study to clarify the effect of cardiac REHAbilitation with multidisciplinary intervention for Chronic Heart Failure of ELDerly patients (J-REHACHF-ELD study) in a super-aged society and ascertain the real figure of HF in elderly patients and efficacy of rehabilitation measures.…”
Section: Introductionmentioning
confidence: 99%